Efficiency effects of tax deductions for work-related expenses - Wolfram F. Richter (Center for Economic Studies and ifo Institute (CESifo), 2004)
In this paper it is shown that allowing the deduction of work-related expenses has a strictly positive effect on tax efficiency only if two conditions hold jointly: (i) The expenses should be interpretable as real cost and (ii) the expenses should be required for increasing taxable income. Otherwise deductions are inefficient, neutral or ambiguous. Thus it is argued that the cost of commuting to work should not be deductible as commuting does not increase taxable income. The efficiency enhancing effect of deducting other expenses like educational ones or expenses for housework and child care is challenged on the grounds that these expenses are largely pecuniary costs.
Keywords: H21; H24; 330; income tax deductions; commuting; housework; child care; educational expenses; efficient taxation; production efficiency; Werbungskosten; Steuerbegünstigung; Steuerwirkung; Optimale Besteuerung; Berufsverkehr; Theorie